Chapter 12 Japanese school lunch and food education - Waida, Yukako (Taylor & Francis, 2022)
School Food, Equity and Social Justice provides contemporary, critical examinations of policies and practices relating to food in schools across 25 countries from an equity and social justice perspective. The book is divided into three sections: Food politics and policies; Sustainability and development; and, Teaching and learning about food. Bringing together an interdisciplinary group of academics with practitioner backgrounds, the chapters in this collection broaden discussions on school food to consider its educational and environmental implications, the ideals of food in schools, the emotional and ideological components of schooling food, and the relationships with home and everyday life. Our aim is to provide enhanced insight into matters of social justice in diverse contexts, and visions of how greater equality and equity may be achieved through school food policy and in school food programs. We expect this book to become essential reading for students, researchers and policy makers in health education, health promotion, educational practice and policy, public health, nutrition and social justice education.